2021
DOI: 10.1039/d0sc05262k
|View full text |Cite
|
Sign up to set email alerts
|

The role of the active site tyrosine in the mechanism of lytic polysaccharide monooxygenase

Abstract: With QM/MM, we investigate the mechanism of tyrosine deprotonation in lytic polysaccharide monooxygenases. Our results support deprotonation and our calculated UV-vis spectra show that two isomers must be formed to match recent experiments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 56 publications
4
40
0
Order By: Relevance
“…In this study, we have shown that simply mimicking the transposition of the histidines or removing the carboxylate at the equatorial position is insufficient to recreate a redox-active copper site. This is in agreement with other studies of the importance of copper coordinating and second-sphere amino acid residues for LPMO activity [18,[40][41][42].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we have shown that simply mimicking the transposition of the histidines or removing the carboxylate at the equatorial position is insufficient to recreate a redox-active copper site. This is in agreement with other studies of the importance of copper coordinating and second-sphere amino acid residues for LPMO activity [18,[40][41][42].…”
Section: Discussionsupporting
confidence: 93%
“…Several reports have suggested a higher affinity of at least some AA9 LPMOs for cellulosic substrates in their Cu + as opposed to their Cu 2+ form (Kracher et al, 2018;Bertini et al, 2018;Courtade et al, 2016;McEvoy et al, 2021). This has also been demonstrated recently for LsAA9_A (Brander, Tokin et al, 2021).…”
Section: Photoreduction Of Lsaa9_a Crystals Soaked With Oligosaccharidesmentioning
confidence: 69%
“…As well as being essential for further reactivity, there are several reports indicating increased polysaccharide affinity on reduction of the active-site metal, suggesting that polysaccharide binding precedes further steps in the mechanism (Kracher et al, 2018;Filandr et al, 2020;Brander, Tokin et al, 2021). Both O 2 and H 2 O 2 have been suggested as natural co-substrates (Bissaro et al, 2017; and the LPMO mechanism is being assessed continuously for the involvement of either/both (Bissaro et al, 2020;Hedega ˚rd & Ryde, 2017;Courtade et al, 2020;McEvoy et al, 2021;Brander et al, 2020). The dependence on H 2 O 2 for saccharide cleavage has been established recently specifically for one of the model LPMOs investigated here (Brander, Tokin et al, 2021), and is generally gaining increasing support.…”
mentioning
confidence: 99%
“…To address the observation of the two radical species, McEvoy et al performed QM/MM to model the feasibility of both deprotonated tyrosyl radical species. 64 The intermediate observed by Singh et al was proposed to be to a cis -[Tyr-CuOH] + formed by hydrogen transfer from the tyrosine hydroxy to an oxyl species in the equatorial plane. The intermediate observed by Paradisi et al was characterized as a trans -[Tyr-CuOH] + which can be formed through internal hydrogen transfer from a water molecule axially coordinated to the copper.…”
Section: Resultsmentioning
confidence: 99%